2007
DOI: 10.1677/joe-07-0446
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that mammalian sex ratios at birth are partially controlled by parental hormone levels around the time of conception

Abstract: An attempt is made to summarize the evidence that the offspring sex ratios (proportions male at birth) of mammals (including man) are causally related to the hormone levels of both parents around the time of conception. Almost all of the cited studies were reported by non-endocrinologists. This being so, it would seem desirable to have comments of endocrinologists on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 62 publications
(72 reference statements)
3
97
1
Order By: Relevance
“…This ratio is conventionally expressed as the ratio of male live births divided by total live births (M/F). The reason for this discrepancy is uncertain but several factors have been proposed (2).…”
Section: Introductionmentioning
confidence: 99%
“…This ratio is conventionally expressed as the ratio of male live births divided by total live births (M/F). The reason for this discrepancy is uncertain but several factors have been proposed (2).…”
Section: Introductionmentioning
confidence: 99%
“…Other theories such as GRANT (1994) andJAMES (1996) generate similar predictions and have linked testosterone levels to human sex ratios. For instance, Grant's Maternal Dominance hypothesis suggests that relatively more dominant mothers have a higher likelihood of male offspring.…”
Section: Introductionmentioning
confidence: 68%
“…Sex ratios can be influenced by numerous factors (Edwards 1966;Jacobsen et al 1999;James 1976James , 1985James , 1987aJames , 1987bJames , 1995James , 1996James , 2001James , 2008McWhirter 1956;Pickles et al 1982). Edmond Malinvaud (1955) studied almost 4 million births in France for [1946][1947][1948][1949][1950] and concluded that the probability estimate p (mea sured as a percentage) of a pregnancy producing a boy is fairly well fitted by the linear relationship p = 51.45 + 0.3n − 0.5m, where n is the number of preexisting boys and m is the number of preexisting girls in the sibship.…”
Section: Discussionmentioning
confidence: 99%